Miniaturized Technologies for Enhancement of Motor Plasticity - Moorjani, Samira (Frontiers in Bioengineering and Biotechnology, 2016)
The idea that the damaged brain can functionally reorganize itself ⎯ so when one part fails, there lies the possibility for another to substitute ⎯ is an exciting discovery of the twentieth century. We now know that motor circuits once presumed to be hardwired are not, and motor-skill learning, exercise, and even mental rehearsal of motor tasks can turn genes on or off to shape brain architecture, function and, consequently, behavior. This is a very significant alteration from our previously static view of the brain, and has profound implications for the rescue of function after a motor injury. Presentation of the right cues, applied in relevant spatiotemporal geometries, is required to awaken the dormant plastic forces essential for repair. The focus of this review is to highlight some of the recent progress in neural interfaces designed to harness motor plasticity, and the role of miniaturization in development of strategies that engage diverse elements of the neuronal machinery to synergistically facilitate recovery of function after motor damage.